INOVASI PRODUK STIK DARI OLAHAN AMPAS TAHU SEBAGAI UPAYA UNTUK MENGEMBANGKAN UMKM DESA SIKUR, KECAMATAN SIKUR, KABUPATEN LOMBOK TIMUR - Sukrisna , Bakti; Aprilia, Bq. Novi; Qauliyah, Nurul; Saba, Angga Putra Yoga; Apriliana, Apriliana; Ramadhini, Auliya; S., Galuh Ayuningtyas; Hairudin, Hairudin; Hermansyah, Hermansyah; Kurniati, Hesti; Ridho, Muhammad (Universitas Mataram, 2023)
Sikur Village is a village located in Sikur District, East Lombok Regency which has 7 hamlets. The Sikur Village community, especially in Kebon Pancor Hamlet, the majority of the population are tofu food makers (home industry). The tofu industry generally produces solid waste in the form of tofu dregs. This waste has not been used optimally. Tofu dregs are usually only used as animal feed. This activity will be directed at the development of stick product innovations from tofu dregs. This activity is also within the framework of the government program UMKM (Micro, Small and Medium Enterprises) development. According to our observations, Sikur Village has not developed optimally. BUMDES as a village-owned enterprise can play a role in this MSME program, so that these goals can be implemented properly. The role of the University of Mataram Thematic KKN Students is highly expected. The programs launched in this activity include empowerment programs consisting of, entrepreneurship socialization, packaging and product legality manufacture as well as marketing development for MSME products and tofu dregs sticks. Tofu dregs sticks were chosen because they are quite easy to manufacture and the raw materials used are cheap so they are expected to have a high selling value. The results of this program are that the people of Sikur Village are able to process tofu dregs into a product that has high economic value, namely Tofu Dregs Sticks, which is expected to be a product that can add product innovation to UMKM (Micro Small and Medium Enterprises) Sikur Village and can develop UMKM (Micro Small Enterprises) Middle School) in Sikur Village.